Are Lough Neagh and the rights of nature the unfinished business of ‘the peace process’? - Doran Peter (Administration)
This article outlines the background to an emergent all-island movement advocating for recognition of the rights of nature – including calls for recognition of Lough Neagh’s right to participate in its community ownership – and proposes that these developments could prefigure a far-reaching transition in our regard for our island home and all its subjects, including the more-than-human. Noting the significance of the fact that prominent voices in the Irish rights of nature movement originated in the borderlands of Derry and Donegal, the paper proposes that the plight of the iconic Lough Neagh in particular presents an unprecedented opportunity for governments in Dublin, Belfast and London to address a blind spot at the heart of the Anglo–Irish ‘peace process’, that is our regard for the intrinsic rights of the land, the waters, and all the communities of species who constitute our island home to flourish. With Ireland’s celebrated eco-philosopher and mystic, John Moriarty, the emergent movement is behind the call to enfranchise the earth and everything in it.